On Comparisons with Ancient Greek Traditions: Lessons from the Mid-Century - Tobolowsky, Andrew (The journal of Hebrew scriptures, 2023)
In the twentieth century, at two crucial instances, comparisons with ancient Greek traditions played an important role in forwarding the argument in favor of the early origins of the pentateuchal narrative: Martin Noth’s "amphictyonic hypothesis" and Frank Moore Cross’s account of the Israelite "epic." This article argues that success of these arguments owes to a hidden "parallelomania" at work in the mid-century, which successfully made the evidence of ancient Greek phenomena seem like something that it was not in service to desirable arguments. Finally, it explores how contemporary approaches can avoid repeating past mistakes.